Futures thinking and the organizational capacity for change of the Rizal Library, Ateneo de Manila University - Palbusa, Maria Cristina N.; Apolinario, Rhea Rowena U.; Lapuz, Elvira B. (Quezon City : School of Library and Information Studies, University of the Philippines Diliman, 2013)
This study aimed to determine the futures thinking of the Rizal Library Staff based on presentation of 26 scenarios in the year 2025 crafted by the Association of College and Research Libraries, a Division of the American Library Association. Along with this futures thinking exercise is an assessment of the organizational capacity for change (OCC) currently prevalent in their workplace using the OCC construct of William Q. Judge, Jr. Each scenario was reviewed on five (5) parameters: the probability that it will occur; the impact if it were to occur; the speed at which it is unfolding; whether it presents an opportunity or threat to research and academic libraries; and the adaptability of the Rizal Library if it were to occur. The result of the futures thinking activity, the collective imagination of the group about the future, was presented using a visualization tool developed by Staley (2009) called a scenario space. The adaptability obtained from the futures thinking exercise was then related to the OCC results.
Vita.
Special Problem (Master of Library and Information Science)--University of the Philippines Diliman
The study utilized the descriptive survey research design with the questionnaire as the primary data gathering tool. The respondents of the study are the Rizal Library Staff. A total of sixty-one (61) questionnaires were distributed with the return rate of 90.16% (n=55). The study revealed that scenarios that were rated as highly probable are scenarios that are technologically-oriented and those that are within the capabilities of the university to provide for. Low probability scenarios are scenarios that depict events that run counter to long standing practices such as the prescribed retirement age of employees and the breaking down of the traditional brick and mortar formal schooling. Majority of the high impact scenarios are those that highlight how advances in technology can alter workflows and challenge long standing paradigms in order to provide service and facilities for a new generation of library clients. The speed at which the scenarios are unfolding were adjudged by the respondents according to the capability and the priorities of the institution to facilitate the changes embodied in the scenarios. Nineteen of the 26 scenarios were considered as opportunity by the Rizal Library Staff while 6 were considered as threats. In terms of adaptability, Rizal Library obtained a score of high adaptability for 6 scenarios and obtained a score of medium adaptability for the rest of the 19 scenarios.
The current organizational capacity for change prevalent within the Rizal Library is at a satisfactory level as evidenced by a high score of 7.52 from a 10-point Likert scale. The Pearson Product Moment Correlation test revealed that the relationship of Rizal Library's adaptability to future scenarios and its OCC is positively moderate.
Keywords: Ateneo de Manila University. -- Rizal Library -- Management; Organizational change -- Philippines -- Case studies; Organizational change -- Philippines -- Management; Forecasting -- Study and teaching; Library employees -- Philippines -- Quezon City